ANALISIS FAKTOR FAKTOR KEPUASAN DAN LOYALITAS ORANG TUA TERHADAP PELAYANAN IMUNISASI BALITA SEBELUM DAN SAAT PANDEMI - Azzahra', Lama'ah (Poltekkes Kemenkes Malang, 2023)
The importance of implementing immunization for children under five is carried out in accordance with the predetermined RPJMN targets. But in reality, immunization coverage in Indonesia is still low, occupying the third position in health problems. During a pandemic, the implementation of immunization is still carried out but must comply with the health protokols that have been determined in order to remain safe and comfortable. The purpose of this study was to identify the factors of satisfaction and loyalty tangible, reliability, responsiveness, assurance, and empathy of parents towards immunization services for children under five before and during the pandemic. This research method uses a literature review study published within the last five years with data sources searching for articles, scientific journals, theses or theses carried out on the Google Scholar database in the 2016 to 2021 period to retrieve articles that are relevant to the suitability of the topic of writing in English. Indonesia. The review method used is the PICOS Framework. The results of this study indicate that there are similarities and differences in the factors of satisfaction and loyalty, namely the tangible, reliability, responsiveness, assurance, and empathy factors of parents towards immunization services for toddlers before and during the pandemic. Especially during a pandemic, all immunization services provided by health workers and workers are adjusted to government recommendations and regulations in complying with health protokols in order to maintain the safety and comfort of parents and toddlers.